Three-dimensional rotational angiography utility in imaging and intervention in a case of pulmonary arteriovenous malformation - NeerajAwasthy; AmolGupta (Wolters Kluwer Medknow Publications, 2021)
Pulmonary arteriovenous malformation (PAVM) is an abnormal communication between the pulmonary artery and the pulmonary vein. PAVMs are usually congenital in origin; however, they may be acquired. Three-dimensional rotational angiography (3DRA) is a technique used increasingly for imaging in congenital heart disease but to our knowledge has never been used in imaging and planning device closure of PAVM. We describe the use of 3DRA technique for imaging and planning device closure of PAVMs and discuss the advantages of this modality. 3DRA is an excellent tool for imaging of various vascular anomalies. It provides high-quality accurate images through a quick and safe procedure, it is also very useful in planning interventional procedures in PAVM, as it clearly delineates all feeders to PAVM and gives an exact view for analysis and intervention.